A clínica do trabalho e o trabalho da clínica: psicoterapia do fazer - Blanco, Rosa Maria Carollo (2007)
To think and to construct a psychological clinic from the psycopathology were a teaching that lode of Carl G. Jung, when the schizophrenia composed its workmanship taking as paradigm. This proposal was taken ahead by James Hillman, extending it for any types of psychic suffering: he suggested that let us see each one as a conscience style, with a proposal ethical and aesthetic that belongs to the suffering and not to its carrier. To compose a clinic that understands the integrant pathology as something in the life and of the life, instead of something to be terminated or to be cured. For this the Kairós Clinic-Workshop was created. As therapeutics, the carried through artisan work in set with a group of carriers of mental riots was chosen. The objective was built to excite a space of making, creating, to coexist, in contraposition to the usual inactivity, paralysis and isolation in the life of this population. An unfolding of this project resulted in one critical retaken of the consecrated clinical procedures and pointed ways to compose other clinics. For this, it is necessary to give passage and listening to the speeches of the psycopathology, instead of, only, diagnosing them or analyzing them